EFEKTIVITAS LAYANAN KONSELING KELOMPOK DENGAN PENDEKATAN ANALISIS TRANSAKSIONAL UNTUK MENGURANGI KEBIASAAN MENGKONSUMSI MINUMAN KERAS PADA REMAJA DUSUN SUREBAYE LAUK DESA BARABALI KECAMATAN BATUKLIANG KABUPATEN LOMBOK TENGAH - Yulianti, Dewi; Wulandari, Indri Sofia (Universitas Hamzanwadi, 2023)
This study aims to provide group counseling services with a transactional analysis approach to reduce the habit of consuming alcohol in teenagers in the surebaye lauk hamlet, Barabali village, Batuliang sub-district, Central Lombok district. This research is a quantitative study with an experimental pre-test post- test design method. The research subjects were 4 teenagers from surebaye lauk village, barabali village. Data collection using a questionnaire. The data analysis technique used descriptive analysis and data hypothesis testing. From the results of data analysis of group counseling services on the ability of adolescents to overcome the habit of consuming alcohol, it was obtained tcount of 3.073 while the number in the t-value table for the one-tailed test (one tail test) with a significance level of 0.05 (5%) at db N = 4 is 2.132. Therefore, the result of data analysis of 3.073 is above the limit of rejection of the null hypothesis which is 2.132 (tcount > ttable), so this study is significant.